Utilization of Synthetic Human Angiotensin II for Catecholamine-Resistant Vasodilatory Shock in Critically Ill Children: A Single-Center Retrospective Case Series - Tezel, Oguzhan; Hutson, Tamara K.; Gist, Katja M.; Chima, Ranjit S.; Goldstein, Stuart L.; Stanski, Natalja L. (Critical care explorations, 2023)
OBJECTIVES: To describe our institutional experience utilizing adjunctive synthetic angiotensin II in critically ill children with catecholamine-resistant vasodilatory shock (CRVS). DESIGN: Single-center, retrospective case series. SETTING: PICU and cardiac ICU (CICU) at a large, quaternary children's hospital in the United States. PATIENTS: Twenty-three pediatric patients with CRVS who were prescribed synthetic angiotensin II at the discretion of bedside clinicians from January 2018 to April 2023. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Twenty-three patients (20 in PICU, 3 in CICU) with a median age of 10.4 years (interquartile range [IQR] 1.5-18.5) received angiotensin II over the study period, 70% of whom died. At the time of angiotensin II initiation, 17 patients (74%) were receiving one or more forms of extracorporeal therapy, and median Pediatric Logistic Organ Dysfunction-2 Score-2 in the prior 24 hours was 9 (IQR 7-11). The median time between initiation of the first vasoactive agent and angiotensin II was 127 hours (IQR 13-289), and the median total norepinephrine equivalent (NED) at initiation was 0.65 μg/kg/min (IQR 0.36-0.78). The median duration of therapy was 27 hours (IQR 4-68), and at each timepoint assessed, patients had median improvement in NED and mean arterial pressure (MAP) with treatment. Survivors initiated angiotensin II nearly 3 days earlier in vasoactive course (91.5 hr vs 161 hr, p = 0.23), and had both greater reduction in NED (-75% [IQR -96 to -50] vs +2.1% [IQR -55 to 33], p = 0.008) and greater increase in MAP (+15 mm Hg [IQR 10-27] vs -1.5 mm Hg [IQR -27 to 18], p = 0.052) at angiotensin II discontinuation. CONCLUSIONS: We demonstrate reduction in NED and improved MAP following initiation of angiotensin II in critically ill children with CRVS. Further prospective work is needed to examine optimal timing of angiotensin II initiation, appropriate patient selection, and safety in this population.